Late phase 1 studies: concepts and outcomes. Issue 10 (October 2021) - Benitez, Jose Carlos; Geraud, Arthur; Texier, Matthieu; Massard, Christophe; Paci, Angelo; Soria, Jean-Charles; Besse, Benjamin
Summary: Over the past two decades, targeted therapies have become cornerstone treatments for numerous cancers with oncogene addiction. Unfortunately, their effectiveness reduces over time and most patients who receive targeted therapies relapse within 12 months. The emergence of drug-resistance mechanisms in tumours paved the way for next-generation inhibitors. However, insufficient concentration of targeted therapy is a frequent but poorly explored mechanism of treatment failure. Additionally, the maximum tolerated dose (MTD) is not always reached in phase studies, and the recommended phase 2 dose is mostly based on benefit–risk ratio and pharmacokinetic considerations, which could result in a suboptimal dose. This scenario has led us to propose a new concept in clinical drug development: the late phase 1 study. The primary goal of this type of trial is to define an alternative MTD of a drug in patients who are chronically exposed and had an initial benefit from targeted therapy but subsequently progressed without an identified resistance alteration. Intrapatient dose escalation might increase drug concentration and restore drug activity or efficacy.